Comparison Between First Line Target Therapy and Immunotherapy in Different Prognostic Categories of BRAF Mutant Metastatic Melanoma Patients: An Italian Melanoma Intergroup Study - Marconcini, Riccardo; Fava, Paolo; Nuzzo, Amedeo; Manacorda, Simona; Ferrari, Marco; De Rosa, Francesco; De Tursi, Michele; Tanda, Enrica Teresa; Consoli, Francesca; Minisini, Alessandro; Pimpinelli, Nicola; Morgese, Francesca; et al. (Frontiers in Oncology, 2022)
BRAF and MEK inhibitors target therapies (TT) and AntiPD1 immunotherapies (IT) are available first-line treatments for BRAF v600 mutant metastatic melanoma patients. ECOG PS (E), baseline LDH (L), baseline number of metastatic sites (N) are well known clinical prognostic markers that identify different prognostic categories of patients. Direct comparison between first-line TT and IT in different prognostic categories could help in first line treatment decision This is a retrospective analysis conducted in 14 Italian centers about 454 metastatic melanoma patients, divided in 3 groups: group A: patients with E=0, L within normal range, and N less than 3; group B: patients not included in group A or C; group C: patients with E>0, L over the normal range, and N more than 3. For each prognostic group we compared TT and IT in terms of PFS, OS, DCR In group A results in 140 TT and 36 IT treated patients were respectively: median PFS 36 vs 12 months (HR HR (95%IC) 1,949 (1,180-3,217) p value0,009); median OS not reached vs 55 months (HR (95%IC) 1,195 (0,602-2,373) p value0,610 ); Disease control rate 99% vs 75% p value <0.001). In group B results in 196 TT and 38 IT treated patients were respectively: median PFS 11.5 vs 5 months (HR 1,535 (1,036-2,275) p value0.033); median OS 19 vs 20 months (HR 0,886 (0,546-1,437) p value0.623); Disease control rate 85% vs 47% p value <0.001) In group C, results in 41 TT and 3 IT treated patients were respectively: median PFS 6.4 vs 1,8 months (HR 4,860 (1,399-16) p value 0,013); median OS 9 vs 5 months (HR 3,443 (0,991-11,9) p value0.052); Disease control rate 66% vs 33% p value 0.612) In good prognosis group A TT showed statistically significant better PFS than IT, also in a long-term period, suggesting that TT can be a good first line option for this patients category. Only in Group B we observed a crossing of the survival curves after the 3rd year of observation in favor of IT. Few patients were enrolled in group C, so few conclusions can be made about it,